Customer Retention in Logistics Industry in India - K, Ranjusha (Digital Repository of Theses, 2024)
The logistics industry plays a critical role in global supply chains, ensuring the timely movement of goods and services across various sectors. In recent years, increasing globalization, technological advancements, and growing environmental concerns have posed significant challenges and opportunities for the logistics sector. This thesis aims to explore and propose strategies to enhance efficiency and sustainability within the logistics industry. This research begins by analyzing the current state of the logistics industry, examining its key components, such as customer behaviour, mindsets, fluctuation of rates, services, customer satisfaction, customer retention & sustainability. By conducting an in-depth review of existing literature and industry reports, the study identifies the major inefficiencies, bottlenecks associated with conventional logistics practices. Furthermore, the thesis investigates emerging trends that have the potential to revolutionize the logistics sector. It explores sustainable logistics practices that encompass environmental, social, and economic dimensions. It investigates the implementation of strategies, such as lowering rates, 24/7 support, better services, increasing trust, personalized services, timely delivery and post service follow ups. The study also examines the role of collaboration and partnerships among stakeholders, including government bodies, industry players, and consumers, in promoting sustainable logistics practices. In addition to operational and collaborative aspects, the thesis delves into the importance of sustainability in the logistics industry. It analyzes the environmental impact of logistics activities and explores strategies to minimize service lapses, losses for the new startups, customer dissatisfaction, promote single window service and enhance overall sustainability in logistics operations. To validate the proposed strategies, the research employs a combination of qualitative & questionnaire methods. This includes case studies, interviews with industry experts, and data analysis. The findings highlight the potential benefits of adopting efficient and sustainable logistics practices, including cost savings, improved customer satisfaction, and enhanced competitiveness by retention of customers. Finally, the thesis concludes by providing a comprehensive framework for enhancing efficiency and sustainability within the logistics industry. This framework integrates the identified technologies, practices, and collaborative approaches, offering a roadmap for logistics companies to transform their operations and contribute to a more sustainable future. This framework serves as a guide for logistics companies, policymakers, and industry stakeholders to navigate the evolving landscape and achieve sustainable growth and success.